Peran Kepuasan Kerja Memediasi Work Life Balance dengan Komitmen Organisasional Generasi Milenial Pada Hotel Non-Bintang - Ida Bagus Ketut Surya; I Gede Riana (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
This study aims to analyse the effect of work life balance on job satisfaction and organizational commitment. This research was conducted at a non-star hotel in Sanur Bali by taking 72 samples of millennial employees. Data was collected by using a questionnaire using a questionnaire. The collected data were analysed using Warp PLS inferential analysis. The results of the study state that work life balance has a significant effect on job satisfaction and organizational commitment. Job satisfaction  have a significant effect on organizational commitment. This study also found that job satisfaction partially mediates the effect of work-life balance on organizational commitment.